2008
DOI: 10.1016/j.jinteco.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Market reactions to export subsidies

Abstract: This paper analyzes the economic impact of export subsidies by investigating stock price reactions to a critical event in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…This paper is also related to a strand of literature in corporate finance, studying the linkages between international activity and stock market variables. Our empirical evidence is consistent with the analysis in Denis, Denis, and Yost (2002), who find that multinational corporations trade at a discount, and with Desai and Hines (2008) and Baker, Foley, and Wurgler (2009), in linking empirically market valuations, returns, and FDI activity. Our approach departs from these contributions in explicitly acknowledging the endogeneity of the variables of interest and in using a structural model to understand the economic forces behind the correlations that we find in the data.…”
Section: Literaturesupporting
confidence: 89%
“…This paper is also related to a strand of literature in corporate finance, studying the linkages between international activity and stock market variables. Our empirical evidence is consistent with the analysis in Denis, Denis, and Yost (2002), who find that multinational corporations trade at a discount, and with Desai and Hines (2008) and Baker, Foley, and Wurgler (2009), in linking empirically market valuations, returns, and FDI activity. Our approach departs from these contributions in explicitly acknowledging the endogeneity of the variables of interest and in using a structural model to understand the economic forces behind the correlations that we find in the data.…”
Section: Literaturesupporting
confidence: 89%
“…By analyzing a sample of Chinese manufacturing firms, Lee et al [46] found that government subsidies are positively related to firm value. Desai and Hines [47] and Girma et al [48] also confirmed that subsidies can improve firm profitability. Yang [49] reported that firms benefit from government subsidies as their production costs decrease and production scales increase, thus creating larger net profits.…”
Section: Relationship Between Government Subsidies and Firm Performancementioning
confidence: 85%
“…Finally, we controlled for financial subsidy, as prior studies [90,91] have established that it may be associated with firm performance. Firms were asked to indicate the financial subsidy that they obtain from authorities.…”
Section: Control Variablesmentioning
confidence: 99%